The Concept of the Death Penalty is Based on Law Number 1 of 2023 Concerning the Criminal Code - Samuel, Christian; Howard, Christopher (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Criminal law as one of the laws that contains various provisions relating to sentencing certainly intends to provide a deterrent effect by giving suffering. One form of punishment that exists and is applied in Indonesia is the death penalty. Since the Dutch East Indies Criminal Code was used in Indonesia, death penalty has also been regulated and used as a sentencing option that can be chosen by a panel of judges in various appropriate cases. The provisions relating to capital punishment are also regulated again in Law Number 1 of 2023 concerning the Criminal Code which is a new regulation relating to criminal law in force in Indonesia. Even though it is regulated again in the new regulation, it is known that there have been several changes and adjustments in Law Number 1 of 2023 concerning the Criminal Code relating to death penalty so it is necessary to pay attention and further scrutiny.